Crowdfunding: As an Alternative to Islamic Funding - Pratiwi, Rizka Estisia; Meirani, Nadia; ., Khumairah (KnE Social Sciences, 2023)
In this digital era, the rapid development of the financial industry has significantly impacted several factors, including financial technology. Fintech services have become the focus of new technology applications, and one of the impactful fintech sectors is crowdfunding. Crowdfunding is a funding model that provides individual investors or a pool of investors to business owners of various new business ventures or social and cultural projects. Based on the crowdfunding phenomenon, there are currently many investors who are interested in funding several types of businesses. However, many investors or business owners are still unfamiliar with crowdfunding schemes, resulting in a lack of confidence in the funding schemes offered. In addition, crowdfunding aligns with the principles of Islamic finance, which avoids usury and promotes the equitable distribution of welfare. This research, based on published studies and indexed by Scopus, focuses on bibliometric research to explore the conceptual development of Islamic crowdfunding. Keywords: crowdfunding, Islamic finance, Shariah compliance, SRI, bibliometric analysis